Experimental analysis of small size solar dryer with phase change materials for food preservation. (January 2021) - Rakshamuthu, S.; Jegan, S.; Joel Benyameen, J.; Selvakumar, V.; Anandeeswaran, K.; Iyahraja, S.
Highlights: Development and experimental analysis of small size greenhouse solar dryer with phase change materials. Evaluation of temperature and moisture content removed. Solar dryer with PCM shows improved temperature and moisture content. Improved drying rate with reduction of drying time. Abstract: The development and performance analysis of a small size greenhouse solar dryer equipped with phase change materials (PCM) for drying food products are reported in this paper. Gooseberries were used as food products for the purpose of drying. The application of phase change material as an energy storage system has become a broad scope for the research in various solar drying processes. The main aim of the present experimental study is to develop a greenhouse solar dryer for drying food products, assisted by zinc nitrate hexahydrate as phase change material and also to investigate the effect of PCM on the performance of the dryer. The comparative study was carried out to assess the performance of open drying process, solar dryer without and with PCM. The moisture content removed, and the temperature of the dryer were evaluated. It was found that using the phase change materials, the temperature and moisture content removed were increased, which led to the enhancement of the drying rate of the products. Hence, the time required for drying has been reduced significantly. Such a kind of small size solar dryer with PCM would be of significance in drying the food products as it would improve the quality of the food products under a hygienic environment.